Virulence of mousepox virus is independent of serpin-mediated control of cellular cytotoxicity - Wallich, Reinhard; Simon, Markus; Müllbacher, Arno (Viral immunology, 2001)
We have investigated whether the differential virulence seen of two Ectromelia (Ect) strains, EctMoscow and ECtHampstead egg, is due to mutation or differential regulation of their serpins (SPI). Poxvirus encoded serine proteinase inhibitors (serpins) have been shown to interfere with cytolytic activity of leukocytes and can also determine virulence. We show that the deduced amino acid sequences of SPI-1, 2, and 3 are identical for the highly virulent EctMoscow and the low virulent EctHampstead strains and that the two viruses express similar potential to inhibit T-cell cytotoxicity, in particular, Fas-mediated target cell lysis, by allorective effectors. Virus titres in wild type B6 mice were effectively controlled very early after inoculation with EctHampstead as compared with EctMoscow, but lack of perforin renders B6 mice similarly susceptible to both virus strains. The data demonstrate that in Ect infection the perforin-mediated cytolytic pathway is not the primary target of serpins and suggest that the apparent attenuation of EctHampstead seen in B6 mice is due to control elements distinct from SPI-1, 2, and 3.